Teaching Grade 10 Girls concepts of the sine trigonometric function using ChatGPT and GeoGebra - Eastes, Malindri (School of Education, 2025)
This research investigates how ChatGPT, a generative AI tool, and GeoGebra, an interactive mathematical software, can be employed to enhance Grade 10 girls' learning experience and comprehension of sine trigonometric function concepts. The study seeks to address the main research question – “How can the use of ChatGPT and GeoGebra as instructional tools enhance the teaching of sine trigonometric function concepts in a Grade 10 mathematics class?”. The study is grounded in the socio-constructivist approach, which emphasizes active student centred learning, and positions teachers as facilitators that promote student engagement during teaching and learning. Trigonometry, particularly concepts related to trigonometric functions, presents significant challenges for South African Grade 12 students. Traditional, teacher centred methods, often based on lectures, may contribute to this limited understanding. A design-based research methodology, utilizing iterative cycles of design, implementation, and refinement was adopted to facilitate the data collection and analyses from the three lessons used. The research sample consisted of 20 Grade 10 girls. Data was gathered through video recordings, worksheets, focus group interviews of students, and teacher interviews. Thematic analysis was conducted to analyze the qualitative data from the data collection instruments. The main findings indicate that GeoGebra enhanced explorative learning and significantly boosted student engagement. ChatGPT was perceived as most effective when it offered step by-step guidance for problem-solving or methods to achieve specific outcomes. Both students and the teacher expressed a preference for using ChatGPT and GeoGebra in tandem, seamlessly switching between the two rather than using each tool in isolation. The simultaneous integration of ChatGPT and GeoGebra in teaching sine trigonometric function concepts promoted independent exploration and critical thinking among students. This study underscores the potential benefits of using both ChatGPT and GeoGebra software in the classroom for teaching sine trigonometric function concepts. The findings highlight the pedagogical value of employing ChatGPT and GeoGebra in teaching sine trigonometric functions, which can be insightful for teacher educators, curriculum advisors involved in professional development for in-service teachers, and mathematics teachers. A limitation of the study is its reliance on a small sample from a single school. Future research could address this by repeating the study with a larger sample that includes students from diverse educational and cultural backgrounds.